Screening And Development Of Herbal Based Anti-Ageing Product - Ali, Insathe Mohamed (2021)
Screening of natural plants such as M. oleifera, H. sabdariffa and A. galanga was conducted in view of developing an anti-ageing product. Those plants have been reported to contain compounds with antioxidant properties which is one of the most important factors that impart anti-ageing effect. However, only one plant which proved to be the most suitable and promising was chosen. A simple extraction method was carried out with ethanol and water before further analysis. Antioxidant assays, namely radical scavenging activity, total phenolic content and total flavonoid content of the plant extracts were investigated. DPPH assay indicated that aqueous extract of H. sabdariffa showed the highest radical scavenging activity with IC50 of 327.0 ± 0.1 μg/ml and followed by hydroethanolic extract of H. sabdariffa with IC50 of 514.5 ± 0.1 μg/ml and ethanolic extract of A. galanga with IC50 of 531.5 ± 0.1 μg/ml. Hydroethanolic extract of H. sabdariffa showed highest phenolic content with 12.4 ± 0.9 mg GAE/g equivalent and total flavonoid content was highest in ethanolic extract of M. oleifera with 4.2 ± 0.5 mg QE/g equivalent. All the extracts were then tested for their pharmacological effect by using C. elegans as the in vivo model. The nematodes were treated with plant extracts at the concentation of 1, 10, 100 and 1000μg/ml. Ethanolic extract of A. galanga and hydroethanolic extract of H. sabdariffa with the concentration of 100 μg/ml and 1000μg/ml increased the mean lifespan to 21.0 ± 0.5 days and 21.1 ± 0.3 days, which were by 20 to 23% respectively compared to control. Both promising extracts were developed into a final solid dosage form using wet granulation method. Several excipients were tested with the extract and the developed A. galanga granules using corn starch as the excipient was the most stable and compatible. It was then quantified for the active components, kaempferol and quercetin with newly developed and validated HPLC method. Dissolution studies shows that the dissolution rate was enhanced by 60 to 80 % in A. galanga granules compared to the extract. The granules also proved to be stable up to six months in hot and humid storage condition (30°C/75% RH).